DEM Simulation of Biaxial Compression Experiments of Inherently Anisotropic Granular Materials and the Boundary Effects. (30th September 2013) - Tong, Zhao-Xia; Zhang, Lian-Wei; Zhou, Min
Abstract : The reliability of discrete element method (DEM) numerical simulations is significantly dependent on the particle-scale parameters and boundary conditions. To verify the DEM models, two series of biaxial compression tests on ellipse-shaped steel rods are used. The comparisons on the stress-strain relationship, strength, and deformation pattern of experiments and simulations indicate that the DEM models are able to capture the key macro- and micromechanical behavior of inherently anisotropic granular materials with high fidelity. By using the validated DEM models, the boundary effects on the macrodeformation, strain localization, and nonuniformity of stress distribution inside the specimens are investigated using two rigid boundaries and one flexible boundary. The results demonstrate that the boundary condition plays a significant role on the stress-strain relationship and strength of granular materials with inherent fabric anisotropy if the stresses are calculated by the force applied on the wall. However, the responses of the particle assembly measured inside the specimens are almost the same with little influence from the boundary conditions. The peak friction angle obtained from the compression tests with flexible boundary represents the real friction angle of particle assembly. Due to the weak lateral constraints, the degree of stress nonuniformity under flexible boundary is higher than that under rigid boundary.